2003
DOI: 10.1016/s0370-2693(02)03010-1
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of electroweak symmetry breaking in supersymmetry and implications for light superpartners

Abstract: We examine arguments that could avoid light superpartners as an implication of supersymmetric radiative electroweak symmetry breaking. We argue that, from the point of view of string theory and standard approaches to generating the µ term, cancellations among parameters are not a generic feature. While the coefficients relating M Z to parameters in the soft supersymmetry breaking Lagrangian can be made smaller, these same mechanisms lead to lighter superpartner masses at the electroweak scale. Consequently we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…If supersymmetry is indeed the explanation for electroweak sym-metry breaking, then it is appropriate to impose reasonable fine-tuning constraints on the soft parameters. These issues and possible ways to evade constraints have recently been reexamined in [193].…”
Section: Upper Limits On Superpartner Masses and Fine-tuningmentioning
confidence: 99%
See 2 more Smart Citations
“…If supersymmetry is indeed the explanation for electroweak sym-metry breaking, then it is appropriate to impose reasonable fine-tuning constraints on the soft parameters. These issues and possible ways to evade constraints have recently been reexamined in [193].…”
Section: Upper Limits On Superpartner Masses and Fine-tuningmentioning
confidence: 99%
“…Recently, these arguments for light superpartners have been examined to study whether cancellations among different soft parameters such as µ and M 3 , or scalars, could weaken the constraints. Based on typical models, particularly string-motivated models, cancellations are arguably very unlikely because µ and the different soft masses on which electroweak symmetry breaking depends typically arise from rather different physics [193].…”
Section: Current Limits On Superpartner Massesmentioning
confidence: 99%
See 1 more Smart Citation
“…One important concern with the published models is that they can be consistent with electroweak symmetry breaking (EWSB) only by having large cancellations between large contributions to M Z . That is a worrisome property [3], and leads one to question the relevance and implications of such models.…”
Section: Introductionmentioning
confidence: 99%
“…This was discussed in Ref. [20] which concluded that lowering the string scale actually increases the amount of fine-tuning required to produce the correct MZ whilst having relatively heavy scalar masses.…”
Section: Other Aspectsmentioning
confidence: 99%